PENGARUH KEPEMIMPINAN, FOKUS PADA PELANGGAN, MANAJEMEN SUMBER DAYA MANUSIA, DAN PENGENDALIAN DAN PROSES MONITORING BERKUALITAS TERHADAP KINERJA KEUANGAN (STUDI PADA UMKM DI KOTA BANDA ACEH) - Sahibul Izar; M. Rizal Yahya (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study was to determine the effect of leadership, customer focus, human resource management and quality control and monitoring processes on financial performance. This research uses simple random sampling method. the sample in this study amounted to 80 samples. The data source used is primary data obtained by distributing questionnaires. The results showed that leadership, customer focus, human resources management, and quality control and monitoring processes had a positive and significant impact on the financial performance of SMEs in Banda Aceh City.